IMPLEMENTATION OF SMART INDONESIA PROGRAM (PIP) POLICY IN EQUALIZING EDUCATION IN INDONESIA - Musdalifah, Lailatul; Hayat, Hayat (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN-COMMUNITY OF RESEARCH LABORATORY, 2024)
Education is a human right that must be given to every Indonesian citizen, and for that every Indonesian citizen has the right to get quality education according to his interests and talents. The Smart Indonesia Program (PIP) is one of the priority programs of the Ministry of Education and Culture (Kemendikbud) which is a priority in realizing education equity. Article 1 mandates that every citizen has the right to receive education facilitated by the government as a form of implementing the national education system. Based on the mandate in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 12 of 2015 which was later updated to the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 19 of 2016 concerning the Smart Indonesia Program (PIP), the Smart Indonesia Program can be interpreted as